Peran TNI Dalam Kontra Terorisme di Indonesia - Diandra Megaputri Mengko (Jurnal Studi Diplomasi dan Keamanan, 2015)
Complexities of terrorism actions have resulted in the transformation of counter-terrorism strategy. In this context, attempts of combating terrorism would need national, bilateral, regional, and multilateral initiatives. Another important factor is the importance of involving various institutions or organization, both in the government and non-government levels. It leads to sevreal questions, such as to what extend is the defferences role and functions of those various institutions (for instance, Densus 88, TNI, NGOs) in countering terrorism; and how do those institution coordinate their actions? In answering these questions, this paper explains historical role of TNI in countering terrorism, both before and after the separation of TNI and Polri. At the same time, this paper also scrutinise the weakest link betwee both institutions which has raised up their difficulty in coordinating policies and their implementations.